(3cJGH GdcQI GdeJMQcIs - (3GhWhdhbSs
(3ChdgG (B:s
(3GdfbWI GdJi JJMQc MQcI eYJOdI gi GdJi JSjQ ai CReGf eJSGhjI s
(3BNQgG (B:s
(3dCf QM NQL ef eQcR GdcQI Edi OGFQI H A agh YehO Ydi SWM OGFQI H A Pdc eG CQOfGg Je cJGH GdcQI GdeJMQcI dGWhdhbS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1452s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs